PENGGUNAAN MEDIA AUDIO VISUAL DALAM RANGKA PENANAMAN NILAI-NILAI KEAGAMAAN ANAK USIA DINI PADA MASA NEW NORMAL DI TK BUNDO KANDUANG KELURAHAN NAPAR - Windha; Muhiddinur Kamal; Supratman; Arifmiboy (Universitas Pahlawan Tuanku Tambusai, 2022)
This research departs from the phenomenon experienced by teachers at Bundo Kanduang Kindergarten, Napar Village, in general, teachers in kindergarten have not paid attention to modern Audio Visual Media in instilling religious values ​​in early childhood, and when demonstrating learning media the teacher only focuses on demonstrating media, so that the class is less conducive and does not choose effective and efficient media. In the process of instilling religious values ​​in early childhood, schools have not used interesting learning using audio-visual media in the classroom so that children feel happy and comfortable both in terms of attitudes, actions, and train children's memory. This study aims to reveal: the use of audio-visual media in the context of inculcating religious values ​​for early childhood in TK Bundo Kanduang, Napar Village. This research is a qualitative descriptive study that aims to describe, analyze the existing and ongoing conditions in verbal language. The data were collected using observations, interviews, and documentation. In carrying out purpose sampling interviews, namely sampling techniques with certain considerations. Based on the results of the research that the author has done using audio-visual media in the context of instilling religious values ​​in early childhood during the new normal period at Bundo Kanduang Kindergarten, it can be concluded that teachers have used audio-visual media in learning but only use laptops, TV, laptops. , tabe, so it's not good, because it only uses a laptop, TV with a small screen and the picture is not clear enough for students to see. But in learning achievement, students are able to read and memorize short verses, prayer movements. Before watching the teacher's video, adjust the sitting position and prepare the tools that will be needed, and invite children to listen from the video, and the last step is the new teacher evaluating learning. Keyword: Audio Visual Media, Early Childhood Religious Values, New Normal